Küçük pupillalı olgularda fakoemülsifikasyon - (:unkn) unknown (My University, 2005)
Miyotik pupilla, katarakt cerrahının karşılaşabileceği güçlükler arasında yer alır. Küçük pupilla aynı zamanda ciddi intraoperatif komplikasyonları beraberinde getirir. Pupillanın genişletilmesi amacı ile kullanılan yöntemler iris sfinkterini koruyan ve etkileyen yöntemler olarak sınıflandırılabilir. Katarakt cerrahı bu olgularda kullanılabilecek seçenek ve yöntemleri bilmelidir. Kliniğimizde bu olgularda fakoemülsifikasyon esnasında primer olarak tercih edilen yöntem iris sfinkterini koruyan yöntemler ve özellikle de bu başlık altında yer alan viskomidriyazis yöntemidir.

Among the operative challenges faced by the cataract surgeon the miotic pupil is a common obstacle and a condition that is associated with the greatest likelihood for serious intraoperative complications. Methods for enlarging the pupil can be classified as sphincter sparing and sphincter involving methods. The cataract surgeon should be aware of the choices and methods that can be used in these patients. Our clinical approach is to use sphincter sparing methods for enlarging small pupils during phacoemulsification. We primarily prefer the use of viscomydriasis in these particular cases.
Small pupil phacoemulsification
Keywords: Göz Hastalıkları